Expression of antiapoptosis gene survivin in luteinized ovarian granulosa cells of women undergoing IVF or ICSI and embryo transfer: clinical correlations - Varras Michail; Polonifi Katerina; Mantzourani Marina; Stefanidis Konstantinos; Papadopoulos Zacharias; Akrivis Christodoulos; Antsaklis Aris (BMC, 2012)
Abstract Background The purpose of the study was to determine the incidence of survivin gene expression in human granulosa cells during ovarian stimulation in Greek women with normal FSH levels, undergoing IVF or ICSI and to discover any correlation between levels of gene expression and clinical parameters, efficacy of ovulation or outcomes of assisted reproduction. Methods Twenty nine women underwent ovulation induction for IVF or ICSI and ET with standard GnRH analogue-recombinant FSH protocol. Infertility causes were male and tubal factor. Cumulus-mature oocyte complexes were denuded and the granulosa cells were analyzed for each patient separately using quantitative reverse transcription polymerase chain reaction analysis for survivin gene expression with internal standard the ABL gene. Results The ABL and survivin mRNA were detected in granulosa cells in 93.1%. The expression levels of survivin were significantly lower in normal women (male infertility factor) compared to women with tubal infertility factor (p = 0.007). There was no additional statistically significant correlation between levels of survivin expression and estradiol levels or dosage of FSH for ovulation induction or number of dominant follicles aspirated or number of retrieved oocytes or embryo grade or clinical pregnancy rates respectively. Conclusions High levels of survivin mRNA expression in luteinized granulosa cells in cases with tubal infertility seem to protect ovaries from follicular apoptosis. A subpopulation of patients with low levels of survivin mRNA in granulosa cells might benefit with ICSI treatment to bypass possible natural barriers of sperm-oocyte interactions.